Pengaruh Jumlah Penduduk dan Pertumbuhan Ekonomi terhadap Pendapatan Asli Daerah Kota Palangkaraya - Rima Harati (Al-Muhasabah: Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
The purpose of this study is to analyze the influence of population and economic growth on the original regional income (PAD) of Palangkaraya City. The dependent variables in this study are population and economic growth, while the independent variable is original regional income (PAD). The research period used is 2013-2024 in Palangkaraya City. The analytical tools used are multiple regression analysis and classical assumption tests. The results of the analysis indicate that population (X1) simultaneously has no significant effect on the increase in original regional income (PAD) of Palangkaraya City. Economic growth (X2) simultaneously has a significant effect on the increase in original regional income (PAD). Based on classical assumptions, the regression model meets the assumption of normality, multicollinearity is present, and there are no symptoms of heteroscedasticity in the regression model used. There are no symptoms or problems of autocorrelation in the regression model.